2011
DOI: 10.5216/pat.v41i2.13012
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação De Escória Siderúrgica, Calcário E Ureia Em Latossolo Cultivado Com Arroz

Abstract: No Brasil, são produzidas cerca de 6,25 milhões de toneladas de escórias de siderurgia (Medeiros et al. 2009), como subproduto da mineração do ferro e da produção do aço, consideradas as fontes mais abundantes e baratas de silicatos. Assim, os materiais inertes do minério de ferro e do carvão, que não foram reduzidos no processo siderúrgico de formação do aço, combinam-se com o cálcio (ca) e o magnésio (Mg) do calcário, dando origem à es- ABSTRACT RESUMOcória de siderurgia (Pereira 1978). este subproduto é ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…Unlike the results of this study, Prates et al (2011) observed increase in sum of bases and reduction in potential acidity with the application of Ca-Mg silicate on the soil. Corroborating these results, Vidal & Prado (2011) also observed that the application of slag in a Latosol cultivated with rice promoted increase in sum of bases and reduction in potential acidity. The values of potential acidity in the layers of up to 10 and > 10 cm were agronomically classified as Low and Medium, respectively, and the values for sum of bases in the layers of up to 20 and > 20 cm were classified as Very good and Good, respectively, according to Alvarez V. et al (1999).…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…Unlike the results of this study, Prates et al (2011) observed increase in sum of bases and reduction in potential acidity with the application of Ca-Mg silicate on the soil. Corroborating these results, Vidal & Prado (2011) also observed that the application of slag in a Latosol cultivated with rice promoted increase in sum of bases and reduction in potential acidity. The values of potential acidity in the layers of up to 10 and > 10 cm were agronomically classified as Low and Medium, respectively, and the values for sum of bases in the layers of up to 20 and > 20 cm were classified as Very good and Good, respectively, according to Alvarez V. et al (1999).…”
Section: Resultsmentioning
confidence: 55%
“…However, there was an increase in pH compared with the initial soil condition (Table 1) and the results were agronomically classified as High, according to Alvarez V. et al (1999). Although not observed in this study, increases in soil pH with the application of Ca-Mg silicates have been widely reported in the literature (Barbosa et al, 2008;Faria et al, 2008;Korndörfer et al, 2010;Prates et al, 2011;Vidal & Prado, 2011). Table 2.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations